Ethiopian Digital Agro-climate Advisory Platform (EDACaP) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Launched in 2019, EDACaP is currently undergoing a scaling process (EIAR and MoA), in order to increase number of beneficiaries from 82,000 to 18 million smallholders to be part of Ethiopia’s e-agricultural extension system. The complete platform comprises of an agro-climate database hub, climate modelling, crop modelling and dissemination platform.